2016
DOI: 10.3899/jrheum.151212
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Persistence with Methotrexate in Rheumatoid Arthritis: A Systematic Review

Abstract: Objective.Medication adherence in patients with rheumatoid arthritis (RA) is typically suboptimal. Nonadherence has been associated with symptom worsening and increased disability. We systematically reviewed published clinical studies to evaluate methotrexate (MTX) adherence and persistence, factors associated with MTX adherence and persistence, and the effect of MTX nonadherence on clinical outcomes in RA.Methods.MEDLINE and Embase were systematically searched (inception to February 2016) using relevant keywo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 48 publications
7
72
2
7
Order By: Relevance
“…According to studies of adherence with MTX treatment, age, family status (divorce), psychological disorders, ethnic origin, disease activity, MTX dosage, and potential toxicity are associated with poor adherence, although discordant results have been reported for most of these factors . We found that nonadherent patients had a higher level of disease activity at baseline (with a higher DAS28 and a lower HAQ score).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…According to studies of adherence with MTX treatment, age, family status (divorce), psychological disorders, ethnic origin, disease activity, MTX dosage, and potential toxicity are associated with poor adherence, although discordant results have been reported for most of these factors . We found that nonadherent patients had a higher level of disease activity at baseline (with a higher DAS28 and a lower HAQ score).…”
Section: Discussionmentioning
confidence: 55%
“…(33%), the lack of a perceived need for treatment (24%), and worries about adverse effects (24%) . In addition to nonadherence, the 1‐year nonpersistence rate for MTX is high (50%) .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] A systematic review of quantitative studies examining determinants of adherence in patients with RA found that adherence rates are highly variable and there is no consistency in determinants of non-adherence. 9 Due to the complex nature of medication adherence, qualitative studies have the potential to provide a more robust understanding of this phenomenon. 10 Qualitative studies published to date addressing determinants of adherence in people with RA have mainly targeted patients' perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that MTX adherence gradually decreased over time, even though the majority of patients took it correctly during the overall adherence period (75%) and during the implementation period (80%). Rates of MTX adherence vary across studies depending on a variety of factors, including the definition of adherence and the method of measurement used . For example, in claims‐based studies of real‐world data, adherence varied from 80% (MTX monotherapy) and 64% to 72% (MTX combination therapy) when measured by medication possession ratio and from 36% to 50% (csDMARDs, including MTX, prescribed with bDMARDs) when measured by prescriptions of csDMARDs filled .…”
Section: Discussionmentioning
confidence: 99%
“…The current treatment guidelines for RA also recommend the concomitant administration of MTX with biologic DMARDs (bDMARDs) , as prior evidence has shown that the efficacy and drug survival of bDMARDs are increased when given in combination with MTX vs monotherapy . Although MTX use is common, patients may experience adverse events (up to 45%) or inadequate efficacy, which may influence treatment adherence .…”
Section: Introductionmentioning
confidence: 99%